Anti-inflammatory effect of aerial bulblets of Dioscorea japonica Thunb extract through inhibition of NF-κB and MAPK signalling pathway in RAW 264.7. Issue 4 (April 2019) - Hwang, Kyung-A; Hwang, Yu-Jin; Kim, Hoi Seok; Hwang, Hye Jeong; Song, Jin; Kim, Young Jun
Abstract : Background: Yam ( Dioscorea japonica Thunb) is a well-known health food in Korea and is widely distributed in the temperate and tropical regions. Although various medical effects of yam have been demonstrated, there is little current knowledge on the efficacy of Youngyeoja (YYJ; the aerial bulblets of the yam plant), their physiological effects, and their mechanism of action. Methods: To investigate the anti-inflammatory effects of YYJ, we examined the level of inflammatory mediators in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells treated with YYJ extract. Nitric oxide (NO) and prostaglandin E2 (PGE2) levels were determined using enzyme-linked immunosorbent assays. Expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were evaluated using real-time polymerase chain reaction and western blotting. In addition, activation of nuclear factor-kappaB (NF-κB) and mitogen-activated protein kinase (MAPK) was detected using western blotting. Results: Treatment of macrophages with LPS markedly induced the production of NO and PGE2. YYJ treatment inhibited the induction of inflammatory mediators and the expression of iNOS and COX-2. More importantly, LPS-induced phosphorylation of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor (IκB) was suppressed by treatment with YYJ, suggesting YYJ inhibited NF-κB activation. Furthermore, YYJ inhibited the LPS-induced phosphorylation of MAPKs. Conclusion: YYJ was shown to have a potent anti-inflammatory effect in LPS-stimulated RAW 264.7 cells, which may be attributed to its inhibitory effect on NF-κB and MAPK activation, consequently blocking the production of inflammatory factors. Therefore, these results suggest that the YYJ extracts could be used as anti-inflammatory agents.